2012
DOI: 10.1111/pcmr.12024
|View full text |Cite
|
Sign up to set email alerts
|

CXCR7 mediates SDF1‐induced melanocyte migration

Abstract: Melanoblasts are derived from the neural crest and migrate to the dermal/epidermal border of skin and hair bulges. Although melanoblast migration during embryogenesis has been well investigated, there are only a few reports regarding the migration of mature melanocytes. Here, we demonstrate that a chemokine, stromal-derived factor-1 (SDF1, also known as CXCL12), and one of its receptor CXCR7 regulate normal human epidermal melanocyte (NHEM) migration. We found that SDF1 induces the directional migration of NHE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 54 publications
(73 reference statements)
0
37
0
Order By: Relevance
“…The structural reasons for this differential behavior have not been defined. b-Arrestin coupling correlates with receptor trafficking properties and is required for the scavenger function of ACKR2 [152] and ACKR3 [151,166,167], whereas it appears dispensable for ACKR4 internalization and ligand uptake [126] (see Fig. 3C).…”
Section: B-arrestin-dependent Signaling Propertiesmentioning
confidence: 98%
“…The structural reasons for this differential behavior have not been defined. b-Arrestin coupling correlates with receptor trafficking properties and is required for the scavenger function of ACKR2 [152] and ACKR3 [151,166,167], whereas it appears dispensable for ACKR4 internalization and ligand uptake [126] (see Fig. 3C).…”
Section: B-arrestin-dependent Signaling Propertiesmentioning
confidence: 98%
“…Chemokine signalling through CXCL12/CXCR4 is a common mechanism controlling the migration of several cell types along the body axis, such as hematopoietic progenitor cells 40 , vascular endothelial cells 41 , melanocytes 42 and tumour cells 43,44 . In addition to the present results, it has been reported that in the CNS, in addition to CR cells, the migration of cerebellar granule precursors 34 , cortical interneurons 23 , microglia 45 , neural precursor cells 46 , and certain brain tumour cells 33 is also dependent on CXCL12/CXCR4…”
Section: Discussionmentioning
confidence: 99%
“…In this region, non-NCderived mesenchymal cells express Sdf1, suggesting a role for SDF1 signaling transduced exclusively by CXCR7 at this step. Recent studies showed that CXCR7 may promote cell migration 26 or proliferation 27 independently of CXCR4. During heart development, the great arteries derived from cardiac NCs undergo extensive lengthening during septation of the outflow tract.…”
Section: Sdf1 Drives Cardiac Nc Migration and Survival Through The CXmentioning
confidence: 99%